2016
DOI: 10.14236/jhi.v23i1.144
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of an electronic health record did not improve A1c values in Type 2 diabetes

Abstract: AbsTrAcTbackground A major justification for the clinical adoption of electronic health records (EHRs) was the expectation that it would improve the quality of medical care. No longitudinal study has tested this assumption. Objective We used hemoglobin A1c, a recognized clinical quality measure directly related to diabetes outcomes, to assess the effect of EHR use on clinical quality. Methods We performed a five-and-one-half-year multicentre longitudinal retrospective study of the A1c values of 537 type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…For example, introduction and gap categories were generated as they assisted in the writing of the introduction and gap and supplied context for this review of literature; however, quotations included in these categories did not necessarily factor into the results presented. (36) ("electronic health record*":ti,ab,kw OR "electronic medical record*":ti,ab,kw OR "computerized health record*":ti,ab,kw OR "computerized medical record*":ti,ab,kw OR ehr:ti,ab,kw OR "electronic patient record*":ti,ab,kw OR "electronic health record":ti,ab,kw) AND (finance*:ti,ab,kw OR monetary:ti,ab,kw OR economic*:ti,ab,kw OR fiscal:ti,ab,kw OR "economic":ti,ab,kw) AND (clinical:ti,ab,kw OR quality:ti,ab,kw) AND ("follow-up studies":ti,ab,kw OR "follow up stud*":ti,ab,kw OR prognos*:ti,ab,kw OR predict*:ti,ab,kw OR course:ti,ab,kw OR "followup stud*":ti,ab,kw OR efficacy:ti,ab,kw OR complication:ti,ab,kw OR chang*:ti,ab,kw OR effective*:ti,ab,kw OR evaluat*:ti,ab,kw OR imptove*:ti,ab,kw OR indicat*:ti,ab,kw OR impact*:ti,ab,kw OR consequence*:ti,ab,kw OR development*:ti,ab,kw OR result*:ti,ab,kw OR outcome*:ti,ab,kw) AND (adopt*:ti,ab,kw OR implement*:ti,ab,kw) 0 (0) N/A 0 (0) ("electronic health records adoption":ti,ab,kw OR "ehr adoption":ti,ab,kw) AND "financial outcomes":ti,ab,kw 35 (3.6) Years: 2009-2019 42 (4.3) ("electronic health records adoption":ti,ab,kw OR "ehr adoption":ti,ab,kw) AND "financial":ti,ab,kw 3 (0.3) Years: 2009-2019 3 (0.3) ("electronic health records adoption":ti,ab,kw OR "ehr adoption":ti,ab,kw) AND "clinical outcomes":ti,ab,kw 95 (9.8) Years: 2009-2019 104 (10.7) ("electronic health records adoption":ti,ab,kw OR "ehr adoption":ti,ab,kw) AND "clinical":ti,ab,kw a N/A: not applicable. [22].…”
Section: Methodsmentioning
confidence: 99%
“…For example, introduction and gap categories were generated as they assisted in the writing of the introduction and gap and supplied context for this review of literature; however, quotations included in these categories did not necessarily factor into the results presented. (36) ("electronic health record*":ti,ab,kw OR "electronic medical record*":ti,ab,kw OR "computerized health record*":ti,ab,kw OR "computerized medical record*":ti,ab,kw OR ehr:ti,ab,kw OR "electronic patient record*":ti,ab,kw OR "electronic health record":ti,ab,kw) AND (finance*:ti,ab,kw OR monetary:ti,ab,kw OR economic*:ti,ab,kw OR fiscal:ti,ab,kw OR "economic":ti,ab,kw) AND (clinical:ti,ab,kw OR quality:ti,ab,kw) AND ("follow-up studies":ti,ab,kw OR "follow up stud*":ti,ab,kw OR prognos*:ti,ab,kw OR predict*:ti,ab,kw OR course:ti,ab,kw OR "followup stud*":ti,ab,kw OR efficacy:ti,ab,kw OR complication:ti,ab,kw OR chang*:ti,ab,kw OR effective*:ti,ab,kw OR evaluat*:ti,ab,kw OR imptove*:ti,ab,kw OR indicat*:ti,ab,kw OR impact*:ti,ab,kw OR consequence*:ti,ab,kw OR development*:ti,ab,kw OR result*:ti,ab,kw OR outcome*:ti,ab,kw) AND (adopt*:ti,ab,kw OR implement*:ti,ab,kw) 0 (0) N/A 0 (0) ("electronic health records adoption":ti,ab,kw OR "ehr adoption":ti,ab,kw) AND "financial outcomes":ti,ab,kw 35 (3.6) Years: 2009-2019 42 (4.3) ("electronic health records adoption":ti,ab,kw OR "ehr adoption":ti,ab,kw) AND "financial":ti,ab,kw 3 (0.3) Years: 2009-2019 3 (0.3) ("electronic health records adoption":ti,ab,kw OR "ehr adoption":ti,ab,kw) AND "clinical outcomes":ti,ab,kw 95 (9.8) Years: 2009-2019 104 (10.7) ("electronic health records adoption":ti,ab,kw OR "ehr adoption":ti,ab,kw) AND "clinical":ti,ab,kw a N/A: not applicable. [22].…”
Section: Methodsmentioning
confidence: 99%
“…It has been found that information alone does not lead to an improvement in care. A study5 looking at how the use of an electronic health record (EHR) affected the quality of care for patients with diabetes found that EHR use did not improve the clinical quality of diabetic care.…”
Section: Dave’s Storymentioning
confidence: 99%
“…Two papers touch on challenges around clinically important areas: Burke et al, around diabetes2 and Lin et al, about kidney disease 3. Burke’s paper shows a “blip,” a deterioration in diabetes control (measured using glycated haemoglobin – HbA1c) after a computerised medical record system (CMR) was implemented.…”
Section: Benefits and Disbenefits Of Cmr System Implementation And Admentioning
confidence: 99%